2013
DOI: 10.4314/jab.v62i0.86073
|View full text |Cite
|
Sign up to set email alerts
|

Profil des lipides sériques des peuls adultes nomades du Nord-Bénin

Abstract: RESUMEObjectif : Décrire le profil des lipides sériques des sujets adultes peuls nomades du Nord-Bénin. Méthodes et résultats : Il s'agissait d'une étude transversale à visée descriptive et analytique ayant concerné 58 sujets adultes peuls nomades et 61 non peuls. Les paramètres lipidiques ont été dosés par la méthode enzymatique conventionnelle. Les résultats ont montré que les valeurs moyennes de la cholestérolémie totale (3,43 ± 0,62 mmol/L), de la cholestérolémie HDL (0,93 ± 0,29 mmol/L) et de la cholestér… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 16 publications
3
0
3
Order By: Relevance
“…This prevalence was much higher than that found in St Louis (26.5%) and Dakar (7.3%). These results agree with those of Gomina et al, in 2011 where the concentration of HDL was low in the same ethnic group as our study population in both men and women [18].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This prevalence was much higher than that found in St Louis (26.5%) and Dakar (7.3%). These results agree with those of Gomina et al, in 2011 where the concentration of HDL was low in the same ethnic group as our study population in both men and women [18].…”
Section: Discussionsupporting
confidence: 94%
“…The average BMI of this study was approximately equal between the two groups, it is comparable to the average found in the study carried out at Ferlo in 2014 (20.55 ± 4.04) and it is lower than the average BMI found in Dakar (24.04 ± 4.98) [17]. This same phenomenon was also noted in a population of the same nomadic ethnic group from North Benin [18]. It was also found that overweight and obesity were higher among hypertensives than among normotensive subjects.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations